Justice Ontology; A Study of ‘Umar Ibn Al-Khaṭṭāb’s Ijtihād - Ahsan Dawi Mansur; Siti Murtiningsih (Al-Ahkam, 2021)
The paper was conducted to discover the nature of justice in the view of 'Umar Ibn Al-Khaṭṭāb and to reveal his ijtihād from the point of view of a philosophical theory of justice. This research includes philosophical research that is historical-factual about a character with the type of library research then analyzes and presents it in a descriptive form. This paper finds that the essence of justice in the view of 'Umar Ibn Al-Khaṭṭāb is acceptable behavior that is animated by the principle of equality. 'Umar Ibn Al-Khaṭṭāb has applied the principle of equality before the law. He treats reason and revelation in harmony and balance in his ijtihād. 'Umar Ibn Al-Khaṭṭāb drew inspiration from the intellect that Allah had given him by capturing universal values brought by the Koran, such as justice and equality, which are valid forever. This research contributes to the flexibility of 'Umar Ibn Al-Khaṭṭāb in ijtihād, which is imbued with the principle of equality.